TWO WINTER SYNOPTIC SITUATIONS WITH IMPORTANT DIFFERENCES OF AIR TEMPERATURE DISTRIBUTION IN THE SOUTHWESTERN PART OF ROMANIA - F. MOLDOVAN; R. BĂTINAŞ (Aerul şi Apa: Componente ale Mediului, 2013)
The present study analyzes the differences reported between the Banat and Oltenia regions in the air temperature distribution in two synoptic periods from 2012-2013 winter, respectively from 9 to 11 of December 2012 and from 24 to 26 of December 2012. The first period was characterized by very low temperatures in Banat and values much higher in Oltenia, while during the second period, the temperatures were very high in Banat and much lower in Oltenia. Atmospheric circulation associated with orographic barrier was responsible for the differences registered between the two regions.